Research methods - Vu, Xuan Doan (Khoa Quốc tế, ĐHQGHN, 2020)
This module ams to provide the students with a framework for conducting research in a systematic manner in all areas of business. It is also designed to help students inculcate the art of presenting research findings in a lucid and informative way.